Cerebral white matter lesions and regional blood flow are associated with reduced cognitive function in early-stage cognitive impairment - Kuroda, Takeshi; Ono, Kenjiro; Honma, Motoyasu; Asano, Miki; Mori, Yukiko; Futamura, Akinori; Yano, Satoshi; Kanemoto, Mizuki; Hieda, Sotaro; Baba, Yasuhiko; Izumizaki, Masahiko; Murakami, Hidetomo (Frontiers in Aging Neuroscience, 2023)
Background: Differences in the extent of cerebral white matter lesions (WML) and regional cerebral blood flow (rCBF) in early-stage cognitive impairment (ESCI) contribute to the prognosis of cognitive decline; however, it is unclear precisely how WML and rCBF affect cognitive decline in ESCI. Objective: We examined the association between WML, rCBF, and cognitive impairment in the ESCI, using path analysis to clarify how these variables affect each other. Methods: Eighty-three patients who consulted our memory clinic regarding memory loss were included in this study based on the Clinical Dementia Rating. Participants underwent the Mini-Mental State Examination (MMSE), brain magnetic resonance imaging (MRI) for voxel-based morphometry analysis, and brain perfusion single-photon emission computed tomography (SPECT) for rCBF evaluation in cortical regions, using 3D stereotactic surface projection (3D-SSP) analysis. Results: Path analysis was performed on the MRI voxel-based morphometry and SPECT 3D-SSP data, showing a significant correlation between both and MMSE scores. In the most suitable model (GFI = 0.957), correlations were observed between lateral ventricular (LV-V) and periventricular WML (PvWML-V) volumes (standardized coefficient [SC]=0.326, p=0.005), LV-V and rCBF of the anterior cingulate gyrus (ACG-rCBF) (SC=0.395, p < 0.0001), and ACG-rCBF and PvWML-V (SC=0.231, p=0.041). Furthermore, a direct relationship between PvWML-V and MMSE scores was identified (SC=-0.238, p=0.026). Conclusion: Significant interrelationships were observed among the LV-V, PvWML-V, and ACG-rCBF that directly affected the MMSE score in the ESCI. The mechanisms behind these interactions and the impact of PvWML-V on cognitive function require further investigation.